Conserved Mechanism of Bicarbonate-Induced Sensitization of CatSper Channels in Human and Mouse Sperm - Ferreira, Juan J.; Lybaert, Pascale; Puga-Molina, Lis C.; Santi, Celia M. (Frontiers in Cell and Developmental Biology, 2021)
To fertilize an egg, mammalian sperm must undergo capacitation in the female genital tract. A key contributor to capacitation is the calcium (Ca2+) channel CatSper, which is activated by membrane depolarization and intracellular alkalinization. In mouse epididymal sperm, membrane depolarization by exposure to high KCl triggers Ca2+ entry through CatSper only in alkaline conditions (pH 8.6) or after in vitro incubation with bicarbonate (HCO3-) and bovine serum albumin (capacitated conditions). However, in ejaculated human sperm, membrane depolarization triggers Ca2+ entry through CatSper in non-capacitating conditions and at lower pH (pH 7.4) than is required in mouse sperm. Here, we aimed to determine whether these differences reflect species-specific or sperm stage-specific mechanisms of CatSper regulation. We exposed ejaculated mouse and human sperm to high KCl to depolarize the membrane and found that intracellular Ca2+ concentration increased at pH 7.4 in sperm from both species. Conversely, intracellular Ca2+ concentration did not increase under these conditions in mouse epididymal or human testicular sperm. Furthermore, pre-incubation with HCO3- triggered intracellular Ca2+ concentration increase in response to KCl in human testicular sperm. Treatment with protein kinase A inhibitors during exposure to HCO3- inhibited Ca2+ concentration increases in mouse epididymal sperm and in both mouse and human ejaculated sperm. Finally, we show that soluble adenylyl cyclase and increased intracellular pH are required for the intracellular Ca2+ concentration increase in both human and mouse sperm. In summary, our results suggest that – in both human and mouse sperm – HCO3- in semen activates the soluble adenylyl cyclase/protein kinase A pathway, which leads to increased intracellular pH and sensitizes CatSper channels to respond to membrane depolarization to allow Ca2+ influx. Thus, the mechanism of CatSper activation by the seminal plasma appears to be conserved between mouse and human sperm.